Perlindungan hukum terhadap anak dari perlakuan kekerasan orang dewasa - Ika Budi Maryatun (Jurnal Civics: Media Kajian Kewarganegaraan, 2005)
Violence to children happen in many time and spaces over the world. We can find it in our daily life. It tends to increase in numbers year by year. For, it needs a serious attention from all stakeholders. It may occur in many types, such as physical, psychological, sexual, abusive, and exploitative violence. Many factors cause it, i.e. economic, education, and law. Indonesian government try to protect the children by legislate UU no. 23/2002 on Children Protection. This law regulates protection to children who get many kinds of violence in law, crime, children kidnapping, selling, and trading, and also who are being physical, psychological, and sexual victims. Children are vulnerable in experiencing violence, because they physically weak and psychologically not stable. They are also limited in knowledge and experience. For those weaknesses, they are sometimes object of violence and commodity by adults, even by own their relatives. The law is aimed to protect children according to rights in UN convention, which include children right to live, right to grow and develop, right to get protection, and right of participation. Implementasi of the law is regulated nationally and internationally.